Assessing Syrian women's knowledge of breast cancer risk factors, warning signs, and barriers to preventive measures: A cross-sectional study - Haidara Bohsas (13954359) (2023)
Background This study aims to investigate the knowledge of Syrian women about breast cancer risk factors, warning signals, and barriers. Breast cancer is the most common cancer worldwide and the leading cause of cancer death among women. It develops when cells in the breast tissue grow uncontrollably, forming a tumor that can spread to other parts of the body. Materials and Methods This survey was conducted online from September 3 to September 27, 2022, and focused on Syrian women over the age of 18. It was divided into two sections, one focusing on sociodemographic characteristics and the other on breast cancer risk factors, warning signals, and barriers. Results This study found that the majority of the 1305 participants had inadequate knowledge of breast cancer risk factors, warning signs, and barriers. Those with higher levels of education, such as Ph.D. students, had the highest overall scores. The sample was mostly made up of housewives, married women, and women with moderate monthly incomes. Conclusion This research found that Syrian women have inadequate knowledge about breast cancer, including risk factors, warning signs, and barriers. To reduce mortality rates, increase survival rates, and improve early diagnosis, local health organizations should provide awareness courses to emphasize the importance of annual breast exams. Other Information Published in: Cancer Treatment and Research Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ctarc.2023.100717